Multicultural Education in Islamic Education Didactic-Methodical Review - Dhimas Alunandika; Saiful Amien (Edumaspul: Jurnal Pendidikan, 2024)
Multicultural education is a cross-border discourse because it is related to democracy and human rights, social justice, and honesty and tolerance for cultural diversity in plural societies. Multicultural education basically aims to create educational discussions, policy makers in the field of Islamic education, students majoring in education science, and general students. This type of research is Library Research, Any form of basic theory related to the research topic is discussed in the literature review, also known as library research. This research uses a qualitative approach, which means that researchers collect descriptive data, namely written or spoken words of people and their observable behavior. After starting the data, researchers use existing theories to provide explanations. The ultimate goal of multicultural education is that students can not only understand and comprehend the subject matter, but they are also expected to have a strong character to act democratically, pluralistically, and humanistically throughout their lives. Because these three things are the core of multicultural education. The didactic-methodic review of Islamic education in multicultural education usually involves various methods and approaches or methods and approaches because they are concepts that must be incorporated into multicultural education.